Inhibitors of inosine 5′-monophosphate dehydrogenase as emerging new generation antimicrobial agents. Issue 8 (24th May 2019) - Juvale, Kapil; Shaik, Althaf; Kirubakaran, Sivapriya
Abstract : Inosine 5′-monophosphate dehydrogenase (IMPDH) is a vital enzyme involved in the de novo synthesis of guanine nucleotides. Inhibitors of bacterial IMPDH hold great potential as new generation antimicrobial agents. Abstract : Inosine 5′-monophosphate dehydrogenase (IMPDH) is a vital enzyme involved in the de novo synthesis of guanine nucleotides. IMPDH catalyzes a crucial step of converting IMP into XMP that is further converted into GMP. Microbial infections rely on the rapid proliferation of bacteria, and this requires the rate-limiting enzyme IMPDH to expand the guanine nucleotide pool and hence, IMPDH has recently received lots of attention as a potential target for treating infections. Owing to the structural and kinetic differences in the host IMPDH and bacterial IMPDH, a selective targeting is possible and is a crucial feature in the development of new potent and selective inhibitors of bacterial IMPDH. Earlier screening of small molecules revealed a structural requirement for the bacterial/protozoal IMPDH. Early optimization of benzimidazole and benzoxazole scaffolds led to the discovery of new potent and selective inhibitors of pathogenic IMPDH. Further research is vastly focused on the development of highly potent and selective inhibitors of various bacterial IMPDHs. Such studies reveal the importance of this excellent target for treating infectious diseases. The current review focuses on the recent developments in the discovery and development of selective inhibitors of bacterial/protozoal IMPDH with emphasis on the inhibition mechanism and structure–activity relationship.